2022
DOI: 10.3390/diagnostics12102341
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Periprosthetic Hip Joint Infections

Abstract: Introduction: Fungal hip prosthetic joint infections (PJIs) are rare but severe infections. Their incidence has increased in the last decades due to the aging population, as well as due to the increased number of immunosuppressed hosts. The present review of all published fungal PJIs in hip arthroplasties aims to present as much data as possible for both medical and surgical treatment options, so that the best applicable management may be concluded. Methods: A meticulous review of all published fungal hip PJIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…However, preoperative diagnosis of PJI is still di cult due to the emergence of infections caused by speci c pathogens and bacterial bio lm formation. [7][8][9][10][11] Although diagnostic techniques such as leukocyte esterase (LE),defensin, PCR, NGS and others have shown the potential to improve diagnostic accuracy, their high technical complexity and medical costs limit their widespread use. [14][15][16]23 Against this backdrop, our study focused on the clinical utility of readily available The ESR and CRP are important biomarkers re ecting the presence of in ammation in the body.…”
Section: Discussionmentioning
confidence: 99%
“…However, preoperative diagnosis of PJI is still di cult due to the emergence of infections caused by speci c pathogens and bacterial bio lm formation. [7][8][9][10][11] Although diagnostic techniques such as leukocyte esterase (LE),defensin, PCR, NGS and others have shown the potential to improve diagnostic accuracy, their high technical complexity and medical costs limit their widespread use. [14][15][16]23 Against this backdrop, our study focused on the clinical utility of readily available The ESR and CRP are important biomarkers re ecting the presence of in ammation in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that more than 25% of TKA revisions are attributable to PJI [ 20 ], underscoring the importance of timely diagnosis for effective treatment planning and optimal therapeutic outcomes. However, preoperative diagnosis of PJI is still difficult due to the emergence of infections caused by specific pathogens and bacterial biofilm formation [ 1 4 ]. Although diagnostic techniques such as leukocyte esterase (LE), ɑ-defensin, PCR, NGS and others have shown the potential to improve diagnostic accuracy, their high technical complexity and medical costs limit their widespread use [ 10 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the diagnosis of periprosthetic joint infection (PJI) still relies heavily on the culture of pathogenic microorganisms, which is widely considered the "gold standard" [ 1 ]. However, with the emergence of specific pathogen infections such as mycobacteria, Brucella, and fungi and the formation of bacterial biofilms, these factors may diminish the detection rate of pathogens and exacerbate the challenges in PJI diagnosis and treatment [ 2 4 ]. Approximately 5%-42% of PJI patients are estimated to demonstrate negative results for pathogenic microorganisms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetic joint infection (PJI) is a significant complication to an otherwise ordinarily successful procedure and presents a significant issue for post‐clinical management when fungi are present. In a recent review of fungal periprosthetic joint infections comprising of 89 patients, C. albicans was the most common clinical isolate (49.4%), followed by C. parapsilosis (18%) and C. glabrata (12.4%) (84). In another meta‐analysis from 2009 to 2019 it was reported that 286 patients had a fungal periprosthetic infection of the knee, hip, shoulder, or elbow.…”
Section: Candida Biofilms Are Important In Superficial and Deep Infec...mentioning
confidence: 99%